Perioperative Effects Associated With the Surgical Treatment of Degenerative Spondylolisthesis: Interbody Versus No Interbody. Issue 2 (March 2019) - Colman, Matthew W.; Baronne, Lon M.; Brodke, Darrel S.; Woodbury, Ashley M.; Annis, Prokopis; Lawrence, Brandon D.
Abstract : Study Design: This is a retrospective analysis. Objective: The purpose of this study was to compare the clinical, radiographic, and perioperative complication profiles of performing an interbody and posterior arthrodesis (CAGE) versus posterolateral lumbar fusion (PLF) alone in patients undergoing surgery for degenerative spondylolisthesis (DS). Summary of Background Data: DS is a common disorder that, failing nonoperative treatment, may be managed with surgical decompression and concomitant posterior arthrodesis. At present, the risk/benefit ratio of including an additional interbody arthrodesis has not been clearly delineated in the literature. Materials and Methods: We reviewed 174 consecutive patients (118 female and 56 male) diagnosed with single-level DS that met the inclusion/exclusion criteria, from January 1, 2000 to August 1, 2011. Clinical outcomes, fusion rates, radiographic outcomes, and complication profiles were recorded. Results: We identified 174 patients who received a single-level lumbar interbody fusion with posterolateral fusion (CAGE, n=89) or posterolateral fusion alone (PLF, n=85). No difference in patient-reported outcomes or fusion rate was detected between the 2 groups. We did identify better segmental lordosis increase (4.9±3.2 vs. 0.9±1.9 degrees; P =0.001) and interdiscal height change (2.1±2.4 vs. 0.6±1.6 mm) in the CAGE group. Operative time, 199.8±36.6 versus 142.6±28.5 minutes ( P <0.001); blood loss, 355±216.4 versus 269±28.5 mL ( P <0.001); and postoperative radiculitis, 28.9% versus 7.0% ( P =0.003) were worse in the CAGE group compared with the PLF group. Conclusions: The ideal surgical approach when treating patients with DS remains in question. This study suggests, when comparing PLF with or without additional interbody fusion, that the lack of clinical or fusion-related benefit may not justify the higher risk profile including longer surgery, higher blood loss, and increased risk of postoperative radiculitis. Long-term prospective studies are required to further clarify these findings. Level of Evidence: Level III.